Determining Factors of Purchase Intention in Personalized Website Context for Indonesian Consumers - Mutiara Sakina; Syaiful Ali (Journal of Economics, Business, and Accountancy Ventura, 2021)
Personalized services can increase customer satisfaction, encourage emotional consumers, help consumers choose a product, and build relationships between service providers and consumers. This study combines the variables embedded in Technology Acceptance Model (TAM), Theory Planned Behavior (TPB), shopping experience, enjoyment, and trust in a research framework model, to examine factors determiningindividual purchase intentions with personalization features on online shopping sites. This study uses primary data obtained by the online survey method. The number of samples analyzed in this study is 303 e-commerce consumers in Indonesia. This study proves that consumer purchase intentions on websites with personalization are positively and significantly related to three factors: the perceived ease of use, perceived enjoyment, and trust. Furthermore, the results also show that the utilitarian value is more influential on these factors than the hedonic value. Further implications of the research results are also discussed in this paper.